The designer's guide to Figma : master prototyping, collaboration, handoff, and workflow - Schwarz, Daniel (SitePoint, 2023)
Figma is the most complete tool for designing apps, websites, and other types of user interfaces (UIs). Unsurprisingly, it's also the most-used UI design tool according to the 2022 Design Tools Survey. Figma can take product design teams all the way from ideation to high-fidelity prototyping—covering all the design processes in between. It can also facilitate diagramming, collaboration, and research. Figma's design handoff and design system management features can help bridge the gap between design and development. It’s available for Windows, macOS, and as a browser app. In this book, we'll immerse ourselves in everything Figma has to offer as we design a simple web page.